2022
DOI: 10.3390/biomedicines10061242
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Dietary Fiber for the Management of Inflammatory Bowel Disease

Abstract: Crohn’s disease (CD) and ulcerative colitis (UC), two components of inflammatory bowel disease (IBD), are painful conditions that affect children and adults. Despite substantial research, there is no permanent cure for IBD, and patients face an increased risk of colon cancer. Dietary fiber’s health advantages have been thoroughly investigated, and it is recommended for its enormous health benefits. This review article discusses the importance of appropriate fiber intake in managing IBD, emphasizing how optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 99 publications
(169 reference statements)
0
11
0
Order By: Relevance
“…Over time, our growing comprehension of the significance of fiber for gastrointestinal health has highlighted the importance of IBD patients achieving an adequate dietary intake as well [ 4 , 47 ]. Although research studies on the role of fiber in the prevention and treatment of IBD in humans are limited [ 48 ], existing intervention trials have shown that dietary fibers can improve IBD symptoms [ 49 ], enhance health-related quality of life [ 50 ], balance inflammation [ 47 ], modulate immune responses [ 51 ], and help mitigate dysbiosis by restoring the gut microbiome [ 52 ]. Dietary fibers mediate these beneficial effects though byproducts of dietary fermentation of MAC, principally SCFA [ 53 , 54 ], and also by preserving the mucus layer barrier by promoting mucus synthesis and secretion [ 16 , 55 ].…”
Section: Nutritional Recommendations In Ibd About Fiber Intakementioning
confidence: 99%
“…Over time, our growing comprehension of the significance of fiber for gastrointestinal health has highlighted the importance of IBD patients achieving an adequate dietary intake as well [ 4 , 47 ]. Although research studies on the role of fiber in the prevention and treatment of IBD in humans are limited [ 48 ], existing intervention trials have shown that dietary fibers can improve IBD symptoms [ 49 ], enhance health-related quality of life [ 50 ], balance inflammation [ 47 ], modulate immune responses [ 51 ], and help mitigate dysbiosis by restoring the gut microbiome [ 52 ]. Dietary fibers mediate these beneficial effects though byproducts of dietary fermentation of MAC, principally SCFA [ 53 , 54 ], and also by preserving the mucus layer barrier by promoting mucus synthesis and secretion [ 16 , 55 ].…”
Section: Nutritional Recommendations In Ibd About Fiber Intakementioning
confidence: 99%
“…IBD is a global healthcare problem with a sustained increasing incidence, affecting millions of people worldwide, all ages and genders [ 55 , 56 ]. It includes two major forms, Ulcerative Colitis, and Crohn’s Disease, which are distinct chronic inflammatory disorders of the gastrointestinal tract with differences in the pathology and clinical characteristics [ 57 , 58 ]. Ulcerative Colitis is typified by mucosal inflammation and is limited to the colon.…”
Section: Role Of Hydroxytyrosol In Ibdsmentioning
confidence: 99%
“…The anti-inflammatory effect facilitated by the conversion of dietary fiber to short-chain fatty acids (SCFA) by intestinal microbiota has been discussed at length by the recent literature [ 80 , 81 ]. In fact, the inflammation-mediating effects of SCFAs alongside indole compounds and dietary omega-3 polyunsaturated fatty acids has also been attributed to interactions between the gut microbiota and macrophages [ 82 ].…”
Section: Specific Dietary Interventionsmentioning
confidence: 99%